STRUGGLING WITH THE QUESTION OF HOW TO LIVE: TEACHING LITERATURE IN THE UNIVERSITY - Durrant, Geoffrey (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1979)
Why is the study of literature evidently not doing what it is supposed to do, which is to educate the young in a richer sense of life? In an article scrupulously sensitive to the balances involved, Geoffrey Durrant unravels the reasons for the characteristic incapacity of a modern university to communicate a sense of values with any confidence or credibility. Prevailing presumptions about what constitutes scholarship in the field of literary criticism are at odds with the realities experienced by those who give their quiet attention to particular works. He describes with refreshing clarity the simple but uncommon elements of teachership called for by class work in literature, and points out that the undeniable pleasures of such teaching offer the potential common ground on which a new confidence in the profession of English studies should be based.